Could Bordetella pertussis vaccine protect against coronavirus COVID-19?. (September 2020) - Alkholy, Usama M.; Salama, Mohamed E.; Mahmoud, Hagar; Taher, Ahmed; Elsayes, Khaled M.
Abstract: According to the World Health Organization (WHO), as of today, there are 2.165.500 confirmed cases of the novel coronavirus disease (COVID-19) and 145.705 deaths in over 185 countries. Unfortunately, despite the tremendous efforts to develop a vaccine initiated by various leading health institutions all over the world, it may be 18 months before a vaccine against the coronavirus is publicly available. We are proposing a theory about testing the use of the Bordetella pertussis vaccine to protect against COVID-19. We deliver this theory to the scientific community, aiming to raise the concern about it, and to provide us with support by realistic and experimental evidence.